Modelling the sound envelope auditory processing using the non-negative-impulse-response modulation filters concept. Part I. Initial simulations - KUTZNER, D. (Archives of Acoustics, 2006)
This article concerns with a new model of the sound envelope processing in the auditory system. The so-called non-negative-impulse-response (NNIR) modulation filters concept argues that if any form of the acoustic signal envelope filtering took place in the auditory pathway, this process should not be described in terms of a band-pass filtration. This modification of the traditional model of the auditory system temporal resolution, based on the modulation filterbank (MFB) activity, results from the cardinal property of the sound envelope and its neural representation, i.e. neural discharges period histogram, which are unavoidably unipolar signals of non-negative values. It has been assumed that if hypothetical modulation filters existed, they should be characterised by a non-negative-impulse-response and, consequently, the frequency characteristics of such filters might not reveal the band-pass properties. The results of the model investigations are compared with selected psychophysical and physiological data.